I–Xe systematics of the impact plume produced chondrules from the CB carbonaceous chondrites: Implications for the half-life value of 129I and absolute age normalization of 129I–129Xe chronometer. (15th March 2017) - Pravdivtseva, O.; Meshik, A.; Hohenberg, C.M.; Krot, A.N.
Abstract: It is inferred that magnesian non-porphyritic chondrules in the CB (Bencubbin-type) carbonaceous chondrites formed in an impact generated plume of gas and melt at 4562.49 ± 0.21 Ma (Bollard et al., 2015) and could be suitable for the absolute age normalization of relative chronometers. Here xenon isotopic compositions of neutron irradiated chondrules from the CB chondrites Gujba and Hammadah al Hamra (HH) 237 have been analyzed in an attempt to determine closure time of their I–Xe isotope systematics. One of the HH 237 chondrules, #1, yielded a well-defined I–Xe isochron that corresponds to a closure time of 0.29 ± 0.16 Ma after the Shallowater aubrite standard. Release profiles and diffusion properties of radiogenic 129* Xe and 128* Xe, extracted from this chondrule by step-wise pyrolysis, indicate presence of two iodine host phases with distinct activation energies of 73 and 120 kcal/mol. In spite of the activation energy differences, the I–Xe isotope systematics of these two phases closed simultaneously, suggesting rapid heating and cooling (possibly quenching) of the CB chondrules. The release profiles of U-fission Xe and I-derived Xe correlate in the high temperature host phase supporting simultaneous closure of 129 I– 129 Xe and 207 Pb– 206 Pb systematics. The absolute I–Xe age of Shallowater standard is derived from the observed correlation between I–Xe and Pb–Pb ages in a number of samples. It is re-evaluated here using Pb–Pb ages adjusted for an updated 238 U/ 235 U ratio of 137.794 and meteorite specific U-isotope ratios. With the addition of the new data for HH 237 chondrule #1, the re-evaluated absolute I–Xe age of Shallowater is 4562.4 ± 0.2 Ma. The absolute I–Xe age of the HH 237 chondrule #1 is 4562.1 ± 0.3 Ma, in good agreement with U-corrected Pb–Pb ages of the Gujba chondrules (Bollard et al., 2015) and HH 237 silicates (Krot et al., 2005). All I–Xe data used here, and in previous estimates of the absolute age of Shallowater, are calculated using 15.7 ± 0.6 Ma value for 129 I half-life. The slopes of I–Xe – Pb–Pb correlation lines plotted for different sets of samples for Shallowater normalization are always ⩽1. Assuming uranium half-life values are correct; this restricts the half-life of 129 I to ⩽15.7 Ma.